Structure of high-Tc superlattices - Fullerton, E.E. (1992)
Fil: Guimpel, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; University of California-San Diego. Department of Physics; Estados Unidos